Wykorzystanie postaci Stirlitza w rosyjskich memach internetowych - Trendowicz, Marcin (Studia Rossica Posnaniensia, 2022)
The article is devoted to the characteristics of Russian-language internet memes that use or allude to the character of Stierlitz, the legendary intelligence agent created by the writer Yulian Semyonov and adapted for the screen in the TV series Seventeen moments of spring, directed by Tatyana Lioznova. The analysis focuses not only on the memes directly referring to the series and jokes about Stierlitz, but also on examples using associations related to the character and the film (in the textual and/or iconic layer) to humorously illustrate phenomena occurring in contemporary Russia. The first group of memes can be seen as the continuation of the Stierlitz jokes still popular in Russia, while the second group includes memes whose main characters are contemporary Russian political activists and politicians (e.g. Vladimir Putin and Alexei Navalny), as well as those referring to current events in the country and the world (e.g. the coronavirus pandemic and the introduction of the Russian vaccine). In both cases, punchlines from jokes or precedent statements combined with an iconic layer are used to create comic effects.